Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T17:25:29+01:00
2010-03-25T18:21:06+01:00
4)
a) ((-1,2)²)⁻¹ = (-1,2)⁻² = -1/1,44 ≈ -0,69
b) (((63/17)⁵)⁰)⁻¹¹ = 1⁻¹¹ = 1
c) (((-2,49)¹)⁻¹)⁻¹ = (-2,49)¹ = -2,49
d) ((-½)²)⁻¹*(-½) = (-½)⁻²*(-½)¹ = (-½)⁻¹ = -2

5)
a) (5/3)³*(3/10)³*(2/7)³*(-14)³ = (-2)³ = -8
b) (36/25)⁻³:(4⅘)⁻³ = (36/25)⁻³:(24/5)⁻³ = (36/25)⁻³*(5/24)⁻³ = (3/10)⁻³ = 1000/27
c) (4/3)⁻²*(0,75)⁻²*(5/6)⁻²*(1,2)⁻² = (4/3)⁻²*(3/4)⁻²*(5/6)⁻²*(6/5)⁻² = 1⁻² = 1
d) (-1,2)⁷:0,4⁷*(⅓)⁷ = (-3)⁷*(⅓)⁷ = (-1)⁷ = -1

6)
a) 5⁶:5⁴+5⁵*5⁻²-(5²)²+5⁻⁴:5⁻⁶ = 5²+5³-5⁴+5⁻⁴:5⁻⁶ = 5²+5³-5⁴+5² = 5²*(1+5¹-5²+1) = 5²*(1+5-25+1) = 25*(-18) = -450
b) ((2,5)³:(2/5)²)*(2,5)⁻⁴ = ((25/10)³:(2/5)²*(25/10)⁻⁴ = ((25/10)³:(5/2)²*(25/10)⁻⁴ = (25/10)⁻¹*(5/2)² = 10/25*25/4 = 5/2 = 2,5
c) (4⁸*4⁴*4⁻³)/(4⁶*4¹) = 4⁹/4⁷ = 4² = 16